The Combined Effects of Heat Treatment and Epoxy Coatings on the Physical and Impact Properties of Gigantochloa scortechinii Bamboo in Seawater - Rajes K. M. Rajan; Rozli Zulkifli; Mohd Faizal Mat Tahir; Albert Uchenna Ude (Journal of Natural Fibers)
This study explores the effects of epoxy coatings and heat treatment on the properties of Gigantochloa scortechinii bamboo in marine environments. Bamboo strips were subjected to heat treatment at temperatures of 160°C, 170°C, and 180°C, followed by single or double epoxy coatings. The strips were then immersed in seawater at concentrations of 100%, 50%, and 0% for 21 days. The findings revealed that bamboo exposed to 0% seawater experienced significant damage compared to those submerged in higher concentrations. Notably, the double epoxy coatings on strips treated at 170°C led to a substantial reduction in water absorption and thickness swelling across all seawater concentrations. Additionally, the water resistance improved with double coatings, showing optimal performance at varying treatment temperatures: 180°C for 100% seawater, 170°C for 50%, and no treatment for 0%. Impact tests indicated that while dry conditions resulted in increased strength with double coatings on strips treated at 170°C, this strength declined sharply after immersion. In contrast, non-heat-treated strips with a single coating maintained better impact strength across all seawater concentrations. The combined effect improves durability in dry conditions but is less effective in seawater. This discovery contributes to the development of safer and more reliable construction materials.